2006
DOI: 10.1007/s10915-006-9113-9
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Difference Method for Unstructured Grids II: Extension to the Euler Equations

Abstract: An efficient, high-order, conservative method named the spectral difference method has been developed recently for conservation laws on unstructured grids. It combines the best features of structured and unstructured grid methods to achieve high-computational efficiency and geometric flexibility; it utilizes the concept of discontinuous and high-order local representations to achieve conservation and high accuracy; and it is based on the finite-difference formulation for simplicity. The method is easy to imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
101
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 249 publications
(103 citation statements)
references
References 31 publications
1
101
0
1
Order By: Relevance
“…on complex geometries, has been the driving force for the development of higher order schemes for unstructured meshes such as the Discontinuous Galerkin (DG) Method, 1 Spectral Volume (SV) method 12,25 and Spectral Difference (SD) Method. 11,24 The SD method is a newly developed efficient high-order approach based on differential form of the governing equation. It was originally proposed by Liu et al 11 and developed for wave equations in their paper on triangular grids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…on complex geometries, has been the driving force for the development of higher order schemes for unstructured meshes such as the Discontinuous Galerkin (DG) Method, 1 Spectral Volume (SV) method 12,25 and Spectral Difference (SD) Method. 11,24 The SD method is a newly developed efficient high-order approach based on differential form of the governing equation. It was originally proposed by Liu et al 11 and developed for wave equations in their paper on triangular grids.…”
Section: Introductionmentioning
confidence: 99%
“…It was originally proposed by Liu et al 11 and developed for wave equations in their paper on triangular grids. Wang et al 24 extended it to 2D Euler equations on triangular grids and Sun et al 22 further developed it for three-dimensional Navier-Stokes equations on hexahedral unstructured meshes. The SD method combines elements from finite-volume and finite-difference techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The SD method seems considerably simpler to implement than the DG method, and it has been observed by May [8] that it may be regarded as a variant of a pre-integrated nodal DG method. While the SD method has proved robust and productive in a variety of applications [9][10][11][12][13][14][15], doubts have been raised about its stability. In particular it has been suggested that the SD scheme is not stable for higher order triangular elements [16], and sometimes weakly unstable in one dimension depending on the choice of flux collocation points.…”
mentioning
confidence: 99%
“…However, the need for highly accurate methods in applications such as large eddy simulation, direct numerical simulation, computational aeroacoustics etc., has seen the development of higher order schemes for unstructured meshes such as the Discontinuous Galerkin (DG) Method, 1,7 Spectral Volume (SV) method 9,10 and Spectral Difference (SD) Method. 4,5 The SD method is a newly developed efficient high-order approach based on differential form of the governing equation. It was originally proposed by Liu et al 4 and developed for wave equations in their paper on triangular grids.…”
Section: Introductionmentioning
confidence: 99%
“…It was originally proposed by Liu et al 4 and developed for wave equations in their paper on triangular grids. Wang et al 5 (2007) extended it to 2D Euler equations on triangular grids and Sun et al 3 (2007) further developed it for three-dimensional Navier-Stokes equations on hexahedral unstructured meshes. The SD method combines elements from finite-volume and finite-difference techniques, and is particularly attractive because it is conservative, and has a simple formulation and implementation.…”
Section: Introductionmentioning
confidence: 99%